O papel do direito administrativo sancionador no combate à corrupção e a necessária preservação da atividade empresarial: uma análise à luz do princípio da função social da empresa - Lima, Guilherme Corona Rodrigues (2021)
This work aims to analyze the role of sanctioning administrative law in combating corruption in the light of the preservation of business activity. For that, it started from an overview about the anti-corruption legislation in Brazil and in the world, as administrative sanctions existing in Brazil and its form of application as legal entities all in the light of the principle of the company´s social function. Finally, it was intended to set the criteria and limits of this sanctioning activity in such a way that, while not ceasing to commit uplawful acts, the principle of the company´s social function in the application of sanctions is observed in order to guarantee the preservation of jobs, tax collection and preservation of the economy, all with a view to observing the public interest and its unavailability in the administrative administration